1989
DOI: 10.1002/em.2850140406
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis testing in Drosophila. VII. Results of 22 coded compounds tested in larval feeding experiments

Abstract: Twenty-two chemicals were tested for mutagenicity in the sex-linked recessive lethal (SLRL) mutation assay after being fed to Drosophila melanogaster larvae. One compound, maleic hydrazide, was found to be mutagenic. It was tested for the ability to produce reciprocal translocations (RTs) and was positive in that assay as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…These variations in the experimental procedures utilized in the two studies may be responsible for the different results. The importance of larval treatment in mutagen screening was realized by Zimmering et al [1989], but the method was not pursued further since some of the tested chemicals did not respond. Our results indicate that larval treatment may still be valuable in environmental mutagen testing.…”
Section: Drosophila Melanogasteflmentioning
confidence: 99%
“…These variations in the experimental procedures utilized in the two studies may be responsible for the different results. The importance of larval treatment in mutagen screening was realized by Zimmering et al [1989], but the method was not pursued further since some of the tested chemicals did not respond. Our results indicate that larval treatment may still be valuable in environmental mutagen testing.…”
Section: Drosophila Melanogasteflmentioning
confidence: 99%
“…The toxic effects of methacrylonitrile have also been attributed to the in vivo release of cyanide and depletion of glutathione (Hartung 1982). There are few mutagenicity studies on methacrylonitrile; however, the available evidence indicates that the chemical is not genotoxic (Knaap et al 1985;NTP 2000;Zeiger et al 1987;Zimmering et al 1989).…”
mentioning
confidence: 99%
“…Other in vivo studies have not demonstrated any genotoxic potential. Thus, GA did not induce gender-linked recessive lethal mutations in male Drosophila melanogaster treated as either larvae (Zimmering et al, 1989) or adults (Yoon et al, 1985). Peroral dosing with GA did not induce dominant lethal mutation in mice (Tamada et al, 1978) or unscheduled DNA synthesis (UDS) in male rat hepatocytes (Mirsalis et al, 1989).…”
Section: Discussionmentioning
confidence: 99%